Fatigue, Depression, and Anxiety Among Ambulating Multiple Sclerosis Patients - AlSaeed, Safanah; Aljouee, Tamadher; Alkhawajah, Nuha M.; Alarieh, Rola; AlGarni, Hanan; Aljarallah, Salman; Ayyash, Mohsen; Abu-Shaheen, Amani (Frontiers in Immunology, 2022)
Background: Multiple sclerosis (MS) is an inflammatory disease associated with adverse outcomes, including depression, anxiety, fatigue, which may affect physical activity and the quality of life among patients with MS (pwMS). Objective: We aim to assess the prevalence of depression, anxiety, and fatigue among pwMS in Riyadh, Saudi Arabia, and demonstrate any correlation between these factors and physical activity as well as the quality of life (QoL). Methods: A cross-sectional study was conducted in Riyadh, Saudi Arabia. Results: 323 pwMS participated in this study, 83 had anxiety (25.7%) and 44 had depression (13.6%). The majority of participants had depression (70%) and anxiety (57%) levels within normal ranges. The mean of EuroQol Group visual analogue scale (EQ-VAS) score was 80.43 (SD=19.8). 156 (48.3%) out of 323 pwMS had reported fatigue while the others had no fatigue (n=167, 51.7%). The results indicate that only 143 patients (44.3%) had vigorous physical activities during the last 70 days with median days per week of 3 (IQR= 5 – 3) and median minutes per day of 60 (Interquartile range: IQR = 60 – 30). 149 patients (49.2%) had moderate physical activities during the last week with median days per week of 3 (IQR = 5 – 3) and median daily minutes of 40 ((IQR = 60 – 30). 194 patients had walking activities (60.0%) with median days per week of 5 (IQR = 7 – 3) and median minutes per day of 45 (IQR = 60 – 30). The results reveal that fatigue was positively correlated with depression (r = 0.407, p-value < 0.001) and anxiety (r = 0.289, p-value < 0.001). Conclusion: The current study shows depression, anxiety, and fatigue tend to be correlated and clustered together among pwMS in our cohort. However, fatigue is not associated with physical activity. The results of this study are important for the improvement of the clinical management of MS patients.